Implementasi Misi Korporasi Melalui Service Quality Untuk Meningkatkan Penjualan Dalam Industri Perbankan - Edy Junaedi (Jurnal Asy-Syukriyyah, 2012)
The concept and policies of service quality have several different generic names: "customer care", "after care", "the aftermarket", "service recovery", and "customer experience management". All capture the fact that the experience of a product or service can contribute to how well or badly a business does in its market. It is a marketing issue because it affects the growth of the firm. A poor experience will undermine any marketing, no matter how good, because negative word of mouth will work against any marketing claims. Word of mouth communications: expectations will be shaped by communications from sources other than the service provider itself. This can include family, friends and colleagues, but more widely the media and other organisations, such as audit agencies. Personal needs: any customer or user of a service will have what they regard as a set of key personal needs that they expect the service to address. These will vary from service to service and from customer to customer. A clear understanding of these needs is necessary to design an appropriate service. Previous experience: many will have had service encounters before. Their previous experience will in part influence their future …P1FiPexpectations of the service. This can include their past experience of the service in question, but also of other services for public services, expectations will be influenced by experience of similar private services. …P2Fii In order to reach loyalty customer, banks have to give service quality and by doing best in service quality every day and every day, the corporate mission become reality in every day and the end result is sales through service and making loyalty customer is easy.